The Sovereignty of Reason : the Defense of Rationality in the Early English Enlightenment. - Beiser, Frederick C. (Princeton legacy library., 2014)
The Sovereignty of Reason is a survey of the rule of faith controversy in seventeenth-century England. It examines the arguments by which reason eventually became the sovereign standard of truth in religion and politics, and how it triumphed over its rivals: Scripture, inspiration, and apostolic tradition. Frederick Beiser argues that the main threat to the authority of reason in seventeenth-century England came not only from dissident groups but chiefly from the Protestant theology of the Church of England. The triumph of reason was the result of a new theology rather than the devel.